Highly Bright Fluorescence from Dispersed Dimers: Deep‐Red Polymorphs and Wide‐Range Piezochromism. Issue 7 (6th February 2020) - Luo, Qing; Lv, Chunyan; Sheng, Haonan; Cao, Feng; Sun, Jingwei; Zhang, Cheng; Ouyang, Mi; Zou, Bo; Zhang, Yujian
Abstract: Near‐infrared piezochromic materials (PCMs), which show a fluorescence response with a clear color difference and strong penetrability, have important potential applications, but few such organic luminophores have been reported. High‐brightness donor (D)–acceptor (A) luminophores present great potential for preparing near‐IR PCMs with clear color differences. However, the intermolecular π–π interactions are sharply enhanced at high pressures, which is not beneficial for the improvement of the piezochromic properties. Herein, two crystalline polymorphs (TPEB‐α and TPEB‐γ) of a D–π–A‐type dye is presented, which emits deep‐red fluorescence with a high emission efficiency (53.2% and 28.1%, respectively). In crystalline state, dispersed dimers are observed and arranged in a herringbone pattern. Interestingly, each dimer is surrounded by four pairs of twisted tetraphenyl ethylene units, which could disrupt the π–π interactions between adjacent dimers during compression. As a result, this luminophor with dispersed dimeric stacking demonstrates the deep‐red to near‐infrared piezochromic behavior with a remarkable redshift (212 nm) and high sensitivity (19.8 nm GPa −1 ). Abstract : A D–π–A architecture with hybridized local and charge transfer and highly bright fluorescence is developed, and its photoluminescence chromism, polymorphs and dispersed dimer properties are fully investigated. During compression, the dispersed dimers surrounded by twisted tetraphenylethene units demonstrate deep‐red to near‐infrared (870 nm) piezochromic behavior with a remarkable redshift (212 nm) and high sensitivity (19.8 nm GPa −1 ).